Current Issues in the Measurement and Disclosure of Corporate Income Taxes. - Seidler, Lee J.; Stickney, Clyde P. (The Accounting Review, 1979)
ABSTRACT: The information about corporate income taxes disclosed in annual reports has changed significantly since the issuance of Accounting Series Release No. 149 in 1973. Several important issues remain unresolved, however, including the measurement of income tax expense for multiple corporate entities, the application of the indefinite reversal criteria for certain differences between book and taxable income, and the disclosure of current income taxes when the deferral method of accounting for the investment credit is used. Examples from corporate annual reports are used in this article to identify underlying reasons for these reporting concerns, and proposals for improved disclosure are offered.